Reclaiming Justice in Marital Ḥadīth Interpretations: A Netnographic and Mubādalah Analysis of Instagram Discourse - Mika, Almughni; Zamzami, Mukhammad; Lutfi, Muhammad; Hegazy, Wael (ADDIN, 2025)
This study highlights the importance of contextual interpretation in the dissemination of ḥadīths on social media, particularly regarding gender dynamics in marriage. Focusing on the frequently cited ḥadīth about “the wife’s denial of her husband’s kindness,” this research explores how such texts, when shared without adequate context, contribute to gender-biased narratives and reinforce patriarchal stereotypes in online spaces. Employing a netnographic approach, the study examines interactions on Instagram accounts @thesunnah_path and @khalidbasalamahofficial, revealing interpretive patterns which are often lacking critical engagement. To counter this, the research applies the mubādalah framework—an egalitarian hermeneutic emphasizing reciprocity and mutual responsibility in marital relationships. Findings show that decontextualized ḥadīth dissemination risks misinterpretation and exacerbates gender imbalances, while mubādalah offers a constructive alternative that promotes gender justice and equitable values. The study calls for more inclusive and context-aware approaches in digital da‘wa, ensuring that religious teachings align with contemporary ethical and social realities. It affirms the need for transformative interpretive models to prevent religious discourse from being misused or misunderstood in today’s digital age.